The Potential of Parijoto Fruit Extract Fraction (Medinilla speciosa Blume) as Antibiofilm against Staphylococcus aureus Bacteria - Nafi’ah, Luthfiana Nurulin; Ismi Rahmawati; Titik Sunarni (Open Access Indonesian Journal of Medical Reviews, 2024)
Parijoto fruit extract (Medinilla speciosa Blume) contains flavonoids, saponins, tannins, and terpenoids and has antibacterial potential in inhibiting the growth of Staphylococcus aureus bacteria. S. aureus bacteria are bacteria that are capable of forming biofilms. This research aims to determine the potential of extracts and fractions (water, ethyl acetate, and n-hexane) in inhibiting the formation and degradation of S. aureus biofilms. Parijoto fruit was extracted using the maceration method with 96% ethanol solvent. The extract was fractionated using a liquid-liquid partition technique with water, ethyl acetate, and n-hexane as solvents. The antibiofilm activity test against the S. aureus bacteria ATCC 25923 was carried out by treatment inhibiting biofilm formation and biofilm degradation. The method is to read absorbance using a microplate reader with a wavelength of 595 nm. Optical density results to calculate IC50 and EC50 values. The results showed that the extract and fractions (water, ethyl acetate, and n-hexane) had the potential to inhibit the formation and degradation of S. aureus bacterial biofilms. The IC50 of biofilm inhibition in the extract, water fraction, ethyl acetate, and n-hexane against S. aureus bacteria was 2.51; 1.03; 1.10; 1.52 mg/ml. The EC50 value of the biofilm degradation test on the extract, water fraction, ethyl acetate, and n-hexane against S. aureus bacteria was 1.03; 1.17; 1.37; 1.88 mg/ml. The most active fraction of parijoto fruit (Medinilla specosa Blume) in inhibiting and degrading S. aureus bacterial biofilms is the water fraction.